The age of Kali : Indian travels & encounters - Dalrymple, William (New York : Vintage Books, 2012)
As he searched for evidence of Kali Yug, the "age of darkness" predicted by an ancient Hindu cosmology in a final epoch of strife and corruption, Dalrymple encountered a region that thrilled and surprised him. Venturing to places rarely visited by foreigners, he presents compelling portraits of a diverse range of figures. His love for the subcontinent comes across in every page, which makes its chronicles of political corruption, ethnic violence and social disintegration all the more poignant. The result is a dark yet vibrant travelogue, and a unique look at a region that continues to be marked by rapid change and unlimited possibilities as it struggles to reconcile the forces of modernity and tradition.
Introduction -- The North. The age of Kali ; In the kingdom of Avadh ; The city of widows ; Warrior queen: the Rajmata of Gwalior ; East of Eton -- In Rajasthan. The sad tale of Bahveri Devi ; Caste wars ; Sati Mata -- The new India. Two Bombay portraits ; Finger-lickin' bad: Bangalore and the fast-food invaders -- The South. At the court of the fish-eyed goddess ; Under the Char Minar ; Parashakti -- On the Indian Ocean. At Donna Georgina's ; Up the tiger path ; The sorcerer's grave -- Pakistan. Imran Khan: out for a duck ; On the frontier ; Blood on the tracks ; Benazir Bhutto: Mills & Boon in Karachi.
Reprinted. Originally published: London : HarperCollins, 1998
Includes index.
Keywords: Dalrymple, William -- Travel -- India; India -- Description and travel; India -- Social life and customs